Dementia‐friendly community indicators from the perspectives of people living with dementia and dementia‐family caregivers. (21st July 2019) - Wu, Suh‐Mian; Huang, Hsiu‐Li; Chiu, Yi‐Chen; Tang, Li‐Yu; Yang, Pei‐Shan; Hsu, Jung‐Lung; Liu, Chien‐Liang; Wang, Woan‐Shyuan; Shyu, Yea‐Ing L.
Abstract: Aims: To identify dementia‐friendly communities' indicators and their current conditions in Taiwan from the perspectives of people with dementia and dementia‐family caregivers. Design: This qualitative study explored the opinions and experiences of people with dementia and dementia‐family caregivers regarding dementia‐friendly communities. Methods: Participants (16 people with dementia and 20 family caregivers) were recruited from neurological clinics, day care centres for people with dementia and support groups for family caregivers in the Taipei community from July ‐ October, 2016. Data were collected in face‐to‐face interviews, which were tape recorded and transcribed verbatim. Transcripts were analysed by Miles and Huberman's (1994) guidelines. Results: Similar indicators for dementia‐friendly communities were identified in Taiwan as in other countries, including dementia‐friendly care services, dementia‐friendly hospitals, dementia‐friendly community environment, dementia‐friendly transportation, dementia‐friendly stores and shops, dementia friendly people, integrated dementia‐related information and community contribution‐ and ‐involvement opportunities for people with dementia. However, Taiwanese people with dementia and family caregivers described no emphasis on the potential of people with dementia to contribute to developing dementia‐friendly communities and more top‐down expectations for the government's role. Conclusion: These indicators can be a guide for developing and evaluating dementia‐friendly communities in Taiwan. Differences between Taiwan and Western developed countries in indicators for dementia‐friendly communities can be further explored. Community nursing assessment, interventions, and evaluation based on these dementia‐friendly communities indicators can be further developed. Impact: This study developed indicators for dementia‐friendly communities in an Asian country. These indicators can be used as a guide for developing and evaluating dementia‐friendly communities. Abstract : 目的: 根据痴呆患者和痴呆家庭照顾者的意见, 制定痴呆友好社区指标以及台湾目前的痴呆友好社区指标。 设计: 此定性研究主要内容是探讨痴呆患者和痴呆家庭照顾者关于痴呆友好社区指标的观点。 方法: 从2016年7月到10月, 研究参与者(16位痴呆患者和20 位痴呆家庭照顾者)都是来自台北社区的神经学诊所、痴呆患者日托中心、家庭照顾者的相关专业人士。 结果: 得出的台湾痴呆友好社区指标与其他国家类似, 指标包括痴呆友好护理服务、痴呆友好医院、痴呆友好社区环境、痴呆友好交通、痴呆友好商店、痴呆友好人员、完善痴呆信息、社区贡献与痴呆患者参与机会。但是, 台湾的痴呆患者和痴呆家庭照顾者表示并不期待痴呆患者和政府会为建设痴呆友好社区做出贡献。 结论: 台湾痴呆友好社区指标与西方发达国家痴呆友好社区指标的不同值得我们进一步研究。根据痴呆友好社区指标发展社区护理评估、干预措施和评估等。 影响: 此研究发现了亚洲国家痴呆友好社区指标。研究得出的指标可用作指南, 引导发展和评估痴呆友好社区。